New record of two species of munidid squat lobster (Decapoda: Anomura) from the North-West Pacific off Japan - Komai, Tomoyuki; Tsuchida, Shinji; Fujiwara, Yoshihiro (Zootaxa, 2023)
Two species of munidid squat lobsters are newly reported from the North-West Pacific off Japan based on material collected by the recent cruise of R/V Kaimei (KM20-10C cruise) of the Japan Agency for Marine-Earth Science and Technology, exploring seamounts in the marine protected area (MPA): Gonionida kaimei n. sp. and Trapezionida psylla (Macpherson, 1994). Gonionida kaimei n. sp. closely resembles G. tangaroa (Ahyong, 2007) and G. rubrimana (Ahyong, 2007), but morphological characters and living colouration differentiate the new species from the latter two species. Genetic analysis using two molecular markers (mitochondrial COI and 16S rRNA genes) also supports the recognition of the new species. Trapezionida psylla has been recorded from the South-West Pacific, and thus the present material greatly extends the geographic range of the species to the North-West Pacific. The identity of the present specimens is also confirmed by the genetic data, as well as the morphological evidence. This study contributes to documenting the benthic invertebrate fauna of the Japanese MPA.